2018
DOI: 10.2174/1389200219666180124113802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GHB On Psychomotor and Driving Performance

Abstract: GHB causes cognitive and psychomotor impairment and risky driving behavior. Multiple aspects and variables are still waiting clarification, such as the harmful potential of illicit preparations, the effect of precursors and impairing dosages. GHB (and its precursors) must be considered a substantial personal and public risk even in the absence of a clear dose-effects correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…GHB doses up to 10 g/70kg (143 mg/kg) had similar effects to alcohol dosed up to 120 g/70kg (1,714 mg/kg) regarding sedative effects and performance impairment, but less severe memory impairing effects and a shorter time course (Johnson 2013). Thus, despite different methodological approaches (Centola 2018), a dose threshold seems to exist, with lower or moderate doses probably not leading to impairment of psychomotor and driving skills, while GHB doses similar to those used in our study (or higher) pose a potential risk.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…GHB doses up to 10 g/70kg (143 mg/kg) had similar effects to alcohol dosed up to 120 g/70kg (1,714 mg/kg) regarding sedative effects and performance impairment, but less severe memory impairing effects and a shorter time course (Johnson 2013). Thus, despite different methodological approaches (Centola 2018), a dose threshold seems to exist, with lower or moderate doses probably not leading to impairment of psychomotor and driving skills, while GHB doses similar to those used in our study (or higher) pose a potential risk.…”
Section: Discussionmentioning
confidence: 65%
“…The effects of GHB on psychomotor function, and presumably on driving performance, are dose-related (Liechti 2016, Centola 2018). The mean dose administrated in our study was 3333 mg (45–50 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 As a sodium salt of GHB, sodium oxybate can impair driving after being ingested due to profound sleepiness and reduced consciousness, and there have been reports of "sleep driving" in patients while taking it. [40][41][42][43][44][45] However, sodium oxybate has a half-life of only 30-40 minutes, with rapid clearance, reducing the incidence of these medication-related parasomnias. 46 One study assessed driver simulator performance on sodium oxybate and found severe driving impairment one hour after dosing that was similar to drivers with breath alcohol concentrations of 0.08% to 0.1%, which is considered legally impaired for drivers in the US.…”
Section: Sodium Oxybatementioning
confidence: 99%
“…Отдельной проблемой во многих странах является употребление натрия оксибутирата водителями автомобилей из-за отсутствия запаха алкоголя, быстрого выведения из крови при сходном с алкогольным характере опьянения. Типичным поведением водителя, находящегося под действием натрия оксибутирата, являются хаотичное вождение (перестроение, игнорирование дорожных знаков), аномальное поведение (засыпание на красный свет светофора, остановка посередине дороги), дезориентация в пространстве, замедленная речь [9].…”
unclassified